1649. Ceftolozane-Tazobactam or Ceftazidime-Avibactam Versus Best Available Therapy in the Treatment of Difficult-to-Treat Pseudomonas aeruginosa Infections: a Retrospective Comparative Effectiveness Analysis of 195 U.S. Hospitals, 2016–2020. (15th December 2022) - Lawandi, Alexander; Mishuk, Ahmed Ullah; Yek, Christina; Yu, Amy; Li, Xiaobai; Strich, Jeffrey R; Sarzynski, Sadia; Warner, Sarah; Kadri, Sameer S
Abstract: Background: Infections due to Pseudomonas aeruginosa displaying difficult-to-treat resistance (DTR-PA) necessitate the use of sub-efficacious and/or toxic "reserve" antibiotics and are associated with considerable morbidity and mortality. Ceftazidime-avibactam (CAZ-AVY) and ceftolozane-tazobactam (CEF-TAZO) are novel ß-lactam/ß-lactamase inhibitors (BLBLI) that tend to retain in vitro activity against DTR-PA. However, little is known about their in vivo effectiveness compared to reserve agents. Methods: Inpatients aged ≥ 18 years with ≥1 blood, urine, respiratory, or body fluid culture growing DTR-PA who received targeted therapy with either CAZ-AVY, CEF-TAZO, or Best-Available Therapy (BAT) were identified in the Premier Healthcare Database. Primary outcome was in-hospital mortality or discharge to hospice and secondary outcome was length of hospital stay (LOS) for survivors. The primary outcome was compared for CAZ-AVY vs CEF-TAZO and novel agents (CAZ-AVY or CEF-TAZO) vs BAT using overlap weighting and binomial regression with downstream adjustment controlling for patient and treatment characteristics. The secondary outcomes were compared using overlap weighting and poisson regression with downstream adjustment controlling for patient and treatment characteristics. Figure 1. Standardized mean differences between included covariates before and after several matching strategies for patients with DTR-Pseudomonas aeruginosa infections treated with Best Available Therapy versus Ceftazidime-Avibactam or Ceftolozane-Tazobactam Figure 2. Standardized mean differences between included covariates before and after several matching strategies for patients with DTR-Pseudomonas aeruginosa infections treated with Ceftazidime-Avibactam versus Ceftolozane-Tazobactam Results: Between 2016 and 2020, 1, 552 patients with DTR-PA infections were identified at 105 hospitals, of which 202 (13.0%) were treated with CAZ-AVY, 906 (58.4%) with CEF-TAZO, and 444 (28.6%) with BAT. Patient characteristics were similar among treatment groups (Table 1, Table 2). Overall crude mortality was 15.5%. The adjusted risk of mortality was lower in patients treated with CAZ-AVI (12.5%, 95% CI 7.9–17.1) vs CEF-TAZO (18.8%, 95% CI 15.9–21.8) for a risk difference of 6.3% (95% 1.1–11.5, p = 0.02). The novel agents were not associated with a reduced mortality risk when collectively compared to BAT (risk difference -1.1%, 95% CI -5.4; 3.2%). LOS favoured novel agents and were comparable for CAZ-AVY and CEF-TAZO. Conclusion: In this real-world observational study of patients with DTR-PA infections, the novel ß-lactam/ß-lactamase inhibitors were comparably effective against BAT, though the use of CAZ-AVY was associated with a reduced mortality compared to CEF-TAZO. Disclosures: All Authors : No reported disclosures.